2012
DOI: 10.1021/jm201640m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Optimized Adenosine A2A/A1 Receptor Antagonists for the Treatment of Parkinson's Disease

Abstract: The design and characterization of two, dual adenosine A(2A)/A(1) receptor antagonists in several animal models of Parkinson's disease is described. Compound 1 was previously reported as a potential treatment for Parkinson's disease. Further characterization of 1 revealed that it was metabolized to reactive intermediates that caused the genotoxicity of 1 in the Ames and mouse lymphoma L51784 assays. The identification of the metabolites enabled the preparation of two optimized compounds 13 and 14 that were dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 67 publications
(81 reference statements)
1
50
0
Order By: Relevance
“…A library of indeno[1,2‐ d ]pyrimidin‐5‐one derivatives (see compounds 30–33 , Fig. , Table ) has been screened by the Janssen group (Pennsylvania, USA) that detected a promising binding profile for the new tricyclic chemotype . Hit‐optimization furnished very potent A 1 /A 2A dual antagonists with remarkable in vivo potency .…”
Section: Medicinal Chemistry Of A2a Antagonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…A library of indeno[1,2‐ d ]pyrimidin‐5‐one derivatives (see compounds 30–33 , Fig. , Table ) has been screened by the Janssen group (Pennsylvania, USA) that detected a promising binding profile for the new tricyclic chemotype . Hit‐optimization furnished very potent A 1 /A 2A dual antagonists with remarkable in vivo potency .…”
Section: Medicinal Chemistry Of A2a Antagonistsmentioning
confidence: 99%
“…In particular, A 1 antagonists stimulate dopamine release at the presynaptic level, while A 2A antagonists enhance postsynaptic responsiveness to dopamine, revealing a rationale for the development of dual antagonists in PD treatment. In addition, A 1 AR blockade is known to have positive effects on PD‐related cognitive disorders …”
Section: Medicinal Chemistry Of A2a Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case examples linking α-carbon oxidation of cyclic tertiary amines and iminium ions to covalent binding have been reported in the literature, 7−10 which include a report of genotoxicity caused by covalent modification of DNA. 11,12 These results raise the possibility that metabolic bioactivation of rimonabant could have toxicological consequences, especially in view of the key role played by reactive metabolites in the toxicity of many other drugs and foreign compounds. 13 In support of this possibility, recently it has been found that rimonabant exhibits potentiated in vitro toxicity to human liver derived THLE cell lines, which expressed P450 3A4 compared to THLE cells that expressed no P450 activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ZM241385) or guanine (e.g. vipadenant 97 ); some antagonists which are not derived from purines have recently shown efficacy in preclinical models of PD, such as Lu AA47070,98,99 SYN-115 100 and 2-amino-8-(4-methylpiperazine-1-carbonyl)-4-phenyl-5H-indeno[1,2-d]pyrimidin-5-one 101. Preladenant is phase III clinical trials for the treatment of PD 45.…”
mentioning
confidence: 99%